2023
DOI: 10.1111/jcmm.17911
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles‐transmitted long non‐coding RNA MTUS2‐5 promotes proliferation and vascularization of human vascular endothelial cells in patients with Budd–Chiari syndrome

Longfei Zhang,
Benchi Feng,
Zhuxin Zhou
et al.

Abstract: The high rates of misdiagnosis and untreated mortality with regard to Budd–Chiari syndrome (BCS) indicated the need to screen effective biomarkers. The aim of this study was to explore the function of extracellular vesicles (EVs) in patients with BCS as well as associated mechanisms. First, differentially expressed long non‐coding RNAs (lncRNAs) from EVs separated from serum between BCS and healthy controls were screened using microarray analysis. Second, the proliferation, migration and tube formation of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Notably, among the upregulated DEGs, the corticosterone biosynthetic gene Hsd11b1 (Fig 5A) was also found upregulated in the bone marrow of rats treated with a combination of topotecan and oxaliplatin (Davis et al, 2023). Furthermore, the upregulation of the microtubule-associated tumour suppressor gene Mtus2 , shown to limit the metastatic activity of cancer cells (Kuo et al, 2017) and to express a long non-coding RNA Mtus2-5 playing a key role in the angiogenesis of patients with a multifactorial thrombosis condition (Zhang et al, 2023), might be of interest as a downstream target of oxaliplatin IV treatment. Likewise, the upregulated Rasl10b gene encoding a small GTPase with tumour suppressor potential (Zou et al, 2006), which was shown to regulate blood flow in the atrium (Rybkin et al, 2007), could also participate in the antitumoral response downstream of oxaliplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, among the upregulated DEGs, the corticosterone biosynthetic gene Hsd11b1 (Fig 5A) was also found upregulated in the bone marrow of rats treated with a combination of topotecan and oxaliplatin (Davis et al, 2023). Furthermore, the upregulation of the microtubule-associated tumour suppressor gene Mtus2 , shown to limit the metastatic activity of cancer cells (Kuo et al, 2017) and to express a long non-coding RNA Mtus2-5 playing a key role in the angiogenesis of patients with a multifactorial thrombosis condition (Zhang et al, 2023), might be of interest as a downstream target of oxaliplatin IV treatment. Likewise, the upregulated Rasl10b gene encoding a small GTPase with tumour suppressor potential (Zou et al, 2006), which was shown to regulate blood flow in the atrium (Rybkin et al, 2007), could also participate in the antitumoral response downstream of oxaliplatin.…”
Section: Resultsmentioning
confidence: 99%
“…A certain degree of inconsistency between RT-PCR and RNA-seq (around 30-40%) is normal and reasonable, and the two cannot correspond to each other. Studies have shown that the correlation between RNA-seq and RT-PCR is around 0.8, 15.1-19.4% of RNA-seq results do not correspond to RT-PCR, and 1.6-2.8% of nonconcordant sequences are the exact opposite of RT-PCR results [27,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%